A study on customer evaluation of the attributes towards Pioneer Sun-Mix Concrete Sdn. Bhd. Ready-Mix Concrete in Northern Region Specifically Penang / Adnan Hassan - Hassan, Adnan (2000)
This research is conducted upon the business operation of Pioneer Sun-Mix Concrete Sdn. Bhd. It was placed and emphasis on the customer evaluation of the product of Pioneer Sun-Mix Concrete Sdn. Bhd. product. Since the merger with Pioneer Limited from Australia. Pioneer Sun-Mix Concrete Sdn. Bhd. improve themselves in product quality through the assistance of advance technology. Pioneer Sun-Mix Concrete Sdn. Bhd. believes that they are now providing to the market the best quality of product. Believing that they delivering the product at superb performance. Pioneer Sun-Mix Concrete Sdn. Bhd. still leading the market of ready-mix concrete with the same proportion of growth. This study important for the company in the effort of differentiating themselves away from the competitor base on what they have done in marketing activities. The term 'value' however is difficult to be identified clearly as it relate with the awareness, understanding and customer readiness to use it as a requirement towards their product.